La familia en el tratamiento de trastornos de la conducta alimentaria. - Castelo Tigxi, Alan Mauricio (2025)
The family plays a fundamental role in the life of every individual, often providing continuous support and influence throughout different stages of life. In times of change or crisis, such as illness, the way a family responds and engages can significantly impact the course of the problem. This study aims to analyze the role of the family in the treatment of eating disorders in adolescents. A descriptive literature review was conducted using Boolean operators and keywords in both English and Spanish to retrieve relevant sources. To structure and organize the selection process, the PRISMA flow diagram was utilized, and inclusion criteria were applied. The methodological quality of the selected studies was assessed using the Critical Review Form for Quantitative Studies (CRF-QS) as a result, a total of 23 scientific articles published within the last ten years were selected from high-impact databases such as PubMed, Web of Science, Scopus, and ProQuest. The findings indicate that a functional family environment contributes to a more favorable response to the treatment of eating disorders in adolescents. Moreover, the effectiveness of the treatment depends on several factors, including family involvement, the treatment context, and its duration. In conclusion, the family plays a decisive role in the treatment of eating disorders in adolescents, either facilitating or hindering the process. Therefore, interventions should adopt an approach that not only focuses on the individual but also incorporates family dynamics.